2019
DOI: 10.3390/medicines6020057
|View full text |Cite
|
Sign up to set email alerts
|

Greater Height Is Associated with a Larger Carotid Lumen Diameter

Abstract: Background: Previous studies link tall stature with a reduced ischemic stroke risk. One theory posits that tall people have larger cerebral artery lumens and therefore have a lower plaque occlusion risk than those who are short. Previous studies have not critically evaluated the associations between height and cerebral artery structure independent of confounding factors. Methods: The hypothesis linking stature with cerebral artery lumen size was tested in 231 adults by measuring the associations between height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
0
5
1
2
Order By: Relevance
“…Whereas our values for CCA in the males were lower than those from Sweden and those from one study in the US, we had higher values for CCA in our females in comparison to those from Sweden 17,22 . We also had higher values in our males compared with those of the second study from US with relatively lower values in our females to theirs 23 . Our values were higher on both sides for the values published from an Iraqi study 8 , where diameter of right CCA = 0.60 ± 0.7 cm and left CCA = 0.58 ± 0.7 cm.…”
Section: Methodscontrasting
confidence: 51%
See 1 more Smart Citation
“…Whereas our values for CCA in the males were lower than those from Sweden and those from one study in the US, we had higher values for CCA in our females in comparison to those from Sweden 17,22 . We also had higher values in our males compared with those of the second study from US with relatively lower values in our females to theirs 23 . Our values were higher on both sides for the values published from an Iraqi study 8 , where diameter of right CCA = 0.60 ± 0.7 cm and left CCA = 0.58 ± 0.7 cm.…”
Section: Methodscontrasting
confidence: 51%
“…In the US, one study by Krejza et al gave normal values of diameter of CCA of males and females as 0.65 ± 0.98 cm and 0.61 ± 0.80 cm respectively 17 . In another study by Hwaung et al, mean total values for the females (0.62 ± 0.88 cm) were higher than those for the males (0.57 ± 0.79 cm) in same country 23 . This is similar to our study with the diameters of ICA and ECA, where the values for females were higher than those of males.…”
Section: Methodsmentioning
confidence: 78%
“…As the IBW is calculated from BH but not BW 14 , this reflects our findings showing that Qa/IBW and Qa/BH have higher predictive power on AVF functionality than the Qa/actual BW. Although the data regarding upper limb vessels are lacking, it has been reported that the carotid and femoral vessels were positively correlated with individual body height [19][20][21][22] . Moreover, the BH was also positively associated with cardiac output 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Considerando la evidencia epidemiológica de otras poblaciones [3][4][5][8][9][10][11] y los cambios anatómicos y fisiológicos que se han descrito 13,14 , se esperaría una relación inversa entre la estatura y la presión arterial inicial. Sin embargo, en adultos mexicanos la presión arterial basal tendió a ser mayor conforme la estatura fue más alta en ambos sexos, con diferencias más amplias entre los hombres que entre las mujeres.…”
Section: Discussionunclassified
“…La asociación inversa entre estatura y presión arterial podría explicarse por diferentes mecanismos: en individuos de menor estatura el diámetro de los vasos sanguíneos es más pequeño 13,14 ; tienen menor número de capilares y menor elasticidad de los grandes vasos 14 ; así como mayor grosor de la íntima media arterial y mayor afectación por aterosclerosis 14 . Estos mecanismos contribuyen a la disminución del lumen vascular, incrementando las resistencias periféricas 13,14 .…”
Section: Introductionunclassified